Attitude Of Chinese Teenagers Toward Fashion Brands - Jie, Sun (2009)
The purpose of this study i sto explore the relationship between factors and the perception of teenagers towards fashion brands in China. It was proposed thet the four factors are advertising, product , culture and peacocky of China's singleton.